2017
DOI: 10.7596/taksad.v6i4.1157
|View full text |Cite
|
Sign up to set email alerts
|

Using Songs in Developing Intercultural Competence

Abstract: Songs in teaching English are not used to the full extent. To confirm this, we created a set of exercises based on the use of songs to form socio-cultural and regional knowledge, to familiarize students with the culture and way of life of Great Britain, to gain a deeper understanding of the representatives of this linguistic cultural community. The next step was carrying out a survey on revealing the effectiveness of using songs in EFL class, more precisely their effect on the developing of intercultural compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…In a similar vein, Shayakhmetova et al (2017) argue that songs can be successfully used for the development of intercultural competence. They carried 12 out a year-long experiment durning which EFL learners were studying eighteen topics related to British culture and everyday life, using five to six songs interwoven with other activities.…”
Section: Connections Between Music and Foreign Language Learningmentioning
confidence: 97%
“…In a similar vein, Shayakhmetova et al (2017) argue that songs can be successfully used for the development of intercultural competence. They carried 12 out a year-long experiment durning which EFL learners were studying eighteen topics related to British culture and everyday life, using five to six songs interwoven with other activities.…”
Section: Connections Between Music and Foreign Language Learningmentioning
confidence: 97%
“…Griffee (1992) argumenta que a música é universal, pois todos conhecem e estão predispostos a conhecer essa arte, e ela é também culturalmente específica, pois o conteúdo e estilo da canção se espelham em uma cultura particular, podem ser produto dessa cultura, podem refletir e influenciar essa cultura. Shayakhmetova et al (2017), com sua pesquisa, afirmam que a música é um excelente material para desenvolver a competência intercultural no ensino da língua inglesa. Seu uso despertou o interesse dos alunos, eles compreenderam mais a canção, opinaram que a letra tem significado muito mais profundo e apresenta mais informações do que pensavam, com isso eles expressam o desejo de continuar usando a música.…”
Section: De Acordo Comunclassified
“…Gobbi (2001), em sua dissertação "A música como estratégia de aprendizagem no ensino de Língua Inglesa", relatou pesquisas que também discutiram o ensino de línguas por meio da música: Miragaya (1992), Kanel (1996), Griffee (1992), Jourdain (1997), Murphey (1990); todas essas pesquisas compartilham a ideia de que a música ajuda na memorização e contribui para uma atmosfera agradável em sala de aula e enfatizam a repetição da música como uma prática importante para a aprendizagem. Shayakhmetova et al (2017) cita as pesquisas de Murphey (1992), Jalongo e Bromley (1984), Martin (1983), Mitchell (1983), que analisam um corpus de canções populares em língua inglesa. Eles concluíram que as músicas eram ferramentas úteis e significativas para melhorar a qualidade do ensino de línguas estrangeiras.…”
Section: Introductionunclassified
“…In other words, very few studies related ICC to the use of songs. Few studies were found, for example, Shayakhmetova, Shayakhmetova, Ashrapova, and Zhuravleva (2017) investigated the use of songs in developing intercultural competence by creating a set of exercises based on the use of songs. A survey on the effectiveness of using songs in EFL class on the developing of intercultural competence was used as well as a test to check the knowledge of the history and culture of Britain.…”
Section: Introductionmentioning
confidence: 99%